2018
DOI: 10.1038/s41598-018-26325-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the mouse cytochrome P450 family responsible for omega-3 epoxidation of eicosapentaenoic acid

Abstract: Metabolites generated via oxygenation of the omega-3 double bond (omega-3 oxygenation) in eicosapentaenoic acid (EPA) have recently been identified as novel anti-inflammatory lipid mediators. Therefore, oxygenase(s) responsible for this metabolic pathway are of particular interest. We performed genome-wide screening of mouse cytochrome P450 (CYP) isoforms to explore enzymes involved in omega-3 oxygenation of EPA. As a result, 5 CYP isoforms (mouse Cyp1a2, 2c50, 4a12a, 4a12b, and 4f18) were selected and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
0
36
1
Order By: Relevance
“…Lipid extraction was performed as previously reported [29]. Cells were suspended in PBS and transferred to a polypropylene tube.…”
Section: Lipid Extraction From Cells Culture Supernatant and Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid extraction was performed as previously reported [29]. Cells were suspended in PBS and transferred to a polypropylene tube.…”
Section: Lipid Extraction From Cells Culture Supernatant and Plasmamentioning
confidence: 99%
“…Lipid metabolites were analyzed by using a UPLC system (ACQUITY) (Waters, Milford, MA, USA) coupled with mass spectrometry (Orbitrap ELITE) (Thermo Fisher Scientific), with modifications of the previously reported protocol [29]. UPLC application was performed with a 1.7 mm, 1.0 × 150 mm ACQUITY UPLC BEH C18 column (Waters).…”
Section: Lc-ms/ms Analysis Of Free Fas and Their Metabolitesmentioning
confidence: 99%
“…In this issue, we first chemically synthesized a large amount of (±)17,18‐EpETE from EPA and found that, like commercially available Cayman (±)17,18‐EpETE, synthesized (±)17,18‐EpETE showed 2 peaks using HPLC system with chiral column. The bacterial enzyme BM‐3 has been reported to stereoselectively convert EPA into 17( S ),18( R )‐EpETE . We found that BM‐3‐derived 17( S ),18( R )‐EpETE was identical with the second peak of (±)17,18‐EpETE (Figure ).…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, CYPs also are present in the liver, lung, kidney, brain, and skin, suggesting that dietary ω3 PUFAs lead to the production of 17,18‐EpETE in various sites in the body . However, despite the many types of CYPs that exist, it is reported that only five types of CYPs can convert EPA into 17,18‐EpETE in mice, and only nine types have this function in humans . Depending on the CYP type, 17,18‐EpETE is produced in a stereoselective or non‐stereoselective manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation